11-14. hafta duktus venozus dopplerinin nukal kalınlık ölçümü ile birlikte kullanımının fetal prognoza etkileri - (:unkn) unknown (My University, 2006)
Amaç: 11-14. gestasyonel haftalarda nukal translusensi (NT) ölçümü ile duktus venozus (DV) Doppler akım paterninin birlikte tarama yöntemi olarak kullanımının kötü perinatal sonlanımı öngörmedeki rolü araştırıldı. Materyal ve Metod: 317 tekiz gebede DV Doppler akım paterni ve NT kal ınl ığı prospektif olarak değerlendirildi. Bulgular: Fetusların 17'sinde DV Doppler akımı anormaldi. 21 fetusda da NT kalınlığı 95. persentil üzerinde ölçüldü. İkiyuzdoksanüç vakanın gebelikleri problemsiz sonlandı. DV Doppler akımında 'a' dalgası kaybı veya yokluğunun duyarlılık, özgüllük, pozitif ve negatif prediktif değeri, sırasıyla %62.5, %95.9,%29.4 ve %98.9 olarak hesaplandı. Anormal DV Doppler akım paterni ve kalın NT saptanması birlikte kullanıldığında bu değerler sırasıyla %62.S, %97.2, %38.5 ve %98.9 idi. Kalın NT saptanan gurupta, DV Doppler akımının normal olması halinde sağlam bebek doğurma oranı %87,5 iken, bu oranın anormal DV Doppler akımı saptandığında %61,5'e düştüğü hesaplandı. Sonuç: DV Doppler değerlendirmesi kalın NT saptanan gebelerde kötü perinatal sonlanım riski artmış olan vakaların saptanmasında yardımcı olabilir. Ancak, NT normal saptanan vakalarda DV Doppler değerlendirmesinin önemi heüz bilinmemektedir.

Objective: To investigate the role of combined screening with nuchal translucency (NT) thickness measurement and ductus venosus tlow-velocity waveform (DV-FVW) assessment at 11 -14 weeks' gestation in predicting adverse perinatal outcome. Materials and methods: DV flow-velocity waveform and NT were prospectively evaluated in 317 singleton pregnancies. Results: The DV-FVW was abnormal in 17 of the fetuses, NT was above the 95th centile in 21 fetuses. The outcome of pregnancy was normal in 293 fetuses. Eight fetuses had an adverse outcome (4 chromosomal anomalies, 4 structural anomalies). The sensitivity, specificity and positive and negative predictive values of absent or reversed flow during the 'a' wave was 62.5%, 95.9%, 29.4% and 98.9%, respectively. These values were 62.5%, 97.2%, 38.5% and 98.9%, respectively, when DV-FVW abnormalities and increased NT were found simultaneously. In cases with increased NT, the percentage of live births with normal karyotype and no structural defects decreased from 87.5% in normal DV-FVW fetuses to 61.5% in abnormal ones. Conclusion: DV-FVW may have a role in the counselling of parents in the case of enlarged NT by identifying those fetuses with an increased risk of adverse perinatal outcome. However, the value of DV-FVW assessment in cases with normal NT is not clear.
Effects of ductus venosus flow-velocity waveform and nuchal translacency assessment on fetal prognosis between 11-14 weeks of pregnancy
Keywords: Biyofizik; Genel ve Dahili Tıp; Kadın Hastalıkları ve Doğum